Efforts To Overcome Obstacles Faced Related To The Implementation Of Indonesia Armed Forces Authority To Confront Terrorism In Indonesia - Lubis, Arief Fahmi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2020)
The description of acts of terrorism as a crime against the state and is a serious threat to the sovereignty of each country. Terrorist acts in Indonesia can now be qualified as military threats, namely threats using organized armed forces that ar e considered to have capabilities that endanger the sovereignty of the state, the territorial integrity of the country, and the safety of the entire nation. The TNI's efforts to overcome obstacles in dealing with terrorism in Indonesia are carried out in accordance with the Perpu in dealing with it. Through the role of the TNI that is shown to the community and government, showing that the TNI carries out the rights and obligations according to its position, it carries out a function. From looking at these roles, we can illustrate that roles can also be interpreted as individual behavior, which is important for the social structure of society because social beings have a tendency to live in groups. also empirical juridical research, namely conducting studies based on observations of the handling of acts of terrorism in Indonesia involving the TNI. It can be concluded that TNI institutions can be used as material for consideration in the authority to deal with acts of terrorism.